MEMBANGUN MINAT BELAJAR MAHASISWA DALAM PAYUNG KKNI MELALUI PENDEKATAN ANDRAGOGI - SILVIA MARIAH H (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2013)
ABSTRACT University student as young generation need to be built as early as possible so they could explore their inner potential as the tip of spear of nation’s development. They need to be given the chance to propose their opinion so the learning process could work as their interest. The effort that the government do to grow their interest is by formulating curriculum study based on occupation field  necessity called the National Qualification Curriculum of Indonesia (KKNI). Through out this curriculum, learning process oriented to student’s set of problems and designed learning experience based on student’s learning necessity. One of the attempted aprroach through KKNI is andragogy approach. 4 basic assumption of andragogy are: (1) self concept, (2) experience, (3) readiness to study, and (4) learning orientation. Keyword: Learning Interest, KKNI, Andragogy